2011
DOI: 10.4103/0970-4388.79930
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-concentration daily topical fluoride application on fluoride release of giomer and compomer: An in vitro study

Abstract: The fluoride release (ppm) was found to be higher in Giomer when compared with Compomer. The fluoride released from Giomer and Compomer was significantly higher in the acidic demineralising solution than in the neutral remineralising solution. It was found that increasing fluoride exposure significantly increased fluoride release from Giomer and Compomer. It was found that the fluoride release from the subgroups of Giomer and Compomer was in the following order: fluoridated dentifrice twice-daily > fluoridated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 0 publications
3
21
0
3
Order By: Relevance
“…Ancak kompozit rezinler yeniden yüklenme özelliği göstermemektedir. Genel olarak bir materyalin başlangıç florür salımı ne kadar yüksek ise yeniden yüklenme kapasitesi de o kadar yüksektir (11).…”
Section: Demineralizasyonu öNleyici Etki 2 Remineralizasyonu Arttırıunclassified
“…Ancak kompozit rezinler yeniden yüklenme özelliği göstermemektedir. Genel olarak bir materyalin başlangıç florür salımı ne kadar yüksek ise yeniden yüklenme kapasitesi de o kadar yüksektir (11).…”
Section: Demineralizasyonu öNleyici Etki 2 Remineralizasyonu Arttırıunclassified
“…In 2011, Dhull et al (16), compared between Giomer and Compomer in fluoride releasing ability before and after daily topical fluoride application and concluded that, with or without topical application of the fluoridated dentifrice the fluoride release was significantly higher in Giomer than Compomer.…”
Section: Introductionmentioning
confidence: 99%
“…In the structure of giomer restorative materials are glass ionomer particles which have formed from a previous reaction to provide production of glass ionomer. By fluoride aluminium previously entering into a reaction with silicate glass polyacid, giomers which form the glass ionomer matrix are then included in the resin producing silica filler (38).…”
Section: Giomersmentioning
confidence: 99%